Challenges Behind the Numbers: Obstacles in the Management and Reporting of BOS Funds at SDN Mataram City - Akmal Yusuf; Wirawan Suhaedi (Jurnal Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze in depth the factors that hinder the management and reporting of BOS funds at SDN Mataram. By understanding the root causes of the problems faced, it is hoped that the results of this study can provide relevant and practical recommendations to improve the efficiency and effectiveness of BOS fund management and reporting. The data collection technique used in this study is in-depth interviews with informants, and the data analysis method employed is thematic analysis. The research findings reveal several challenges in the management and reporting of BOS funds, including unit price standards (SSH) that are not in line with market prices, disparities between the amount of BOS funds received by schools and the number of operational needs that must be met, and the large number of documents that must be prepared in an insufficient amount of time.